A simplified implementation of the least squares solution for pairwise comparisons matrices - Anholcer, Marcin; Babiy, Volodymyr; Bozóki, Sándor; Koczkodaj, Waldemar W. (Central European journal of operations research, 2011)
This is a follow up to “Solution of the least squares method problem of pairwise comparisons matrix” by Bozóki published by this journal in 2008. Familiarity with this paper is essential and assumed. For lower inconsistency and decreased accuracy, our proposed solutions run in seconds instead of days. As such, they may be useful for researchers willing to use the least squares method instead of the geometric means method.